A multi-criteria decision-making model for hotel selection with linguistic distribution assessments - Yu, Su-min; Wang, Jing; Wang, Jian-qiang; Li, Lin (Applied soft computing, 2018)
[Display omitted] •Numerous online reviews of hotels are described by linguistic distribution assessments that can retain original information effectively.•New comparison method is defined based on linguistic scale functions to break through the restriction of previous comparison method for linguistic distribution assessments.•New distance measurement between linguistic distribution assessments is defined based on the linguistic scale functions to calculate the distance between any two linguistic distribution assessments that have different numbers of linguistic terms.•In order to deal with the conflicting criteria and the preferences for criteria in different groups, a mathematical model is designed based on an extended VIKOR approach and the idea of PA operator to select hotels on tourism websites.•A case study of TripAdvisor.com is conducted to select suitable hotels using online reviews of these hotels. The effect of online reviews on resulting decisions attracted the interests of merchants and researchers in different fields. According to existing studies, the decisions of tourists are highly likely modified after browsing online reviews from other travelers on a tourism website. The manner in which online reviews on tourism websites are utilized to select hotels and support tourists is a noteworthy research problem. Online reviews of a hotel are provided by various tourists with respect to different criteria; thus, each tourist is regarded as a decision-maker. In this instance, the problem of hotel selection is based on online reviews in a tourism website and is expressed as a multi-criteria decision-making problem. In this study, a mathematical model was designed to select appropriate hotels on websites. First, a new comparison method for linguistic distribution assessments was proposed based on linguistic scale functions. Second, a novel distance measurement between linguistic distribution assessments with different numbers of linguistic terms was defined with an adjustable parameter. Third, a model for calculating weights and a mathematical model were constructed according to the idea of prioritized aggregation operator and distance measurement. Finally, a case study of TripAdvisor.com was conducted to select suitable hotels using online reviews of hotels. Data analysis was completed to prove the viability of the designed model.